2018
DOI: 10.18786/2072-0505-2018-46-5-445-463
|View full text |Cite
|
Sign up to set email alerts
|

Social and demographic characteristics, features of disease course and treatment options of inflammatory bowel disease in Russia: results of two multicenter studies

Abstract: О р и г и н а л ь н а я с т а т ь я Белоусова Елена Александровна -д-р мед. наук, профессор, руководитель отделения гастроэнтерологии и гепатологии, заведующая кафедрой гастроэнтерологии факультета усовершенствования врачей 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 45 publications
0
3
0
11
Order By: Relevance
“…An epidemiological study in Russia, for example, found that its European part had 20.4 per 100,000 population for UC and 3.7 per 100,000 population for CD. 19 In one hand, the observed prevalence could partially be explained by the differences in healthcare access, database system, lifestyle and various risk factors as reported previously. 20,21 Another possible explanation might be that Central Asian, including Kazakhstan, has a traditional nomadic diet, which may lie somewhere between West and East Asian cuisines, resulting in intermediate prevalence rates.…”
Section: Impact Of Demographic and Clinical Characteristics On Ibd Awmentioning
confidence: 69%
See 1 more Smart Citation
“…An epidemiological study in Russia, for example, found that its European part had 20.4 per 100,000 population for UC and 3.7 per 100,000 population for CD. 19 In one hand, the observed prevalence could partially be explained by the differences in healthcare access, database system, lifestyle and various risk factors as reported previously. 20,21 Another possible explanation might be that Central Asian, including Kazakhstan, has a traditional nomadic diet, which may lie somewhere between West and East Asian cuisines, resulting in intermediate prevalence rates.…”
Section: Impact Of Demographic and Clinical Characteristics On Ibd Awmentioning
confidence: 69%
“…In general, the situation concerning the IBD prevalence in Asian countries is very similar to a West-East gradient of 2:1 in IBD incidence in Europe [ 18 ], but with lower rates. An epidemiological study in Russia, for example, found that its European part had 20.4 per 100,000 population for UC and 3.7 per 100,000 population for CD [ 19 ]. In one hand, the observed prevalence could partially be explained by the differences in healthcare access, database system, lifestyle and various risk factors as reported previously [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…В России в течение последнего десятилетия были проведены 2 наиболее крупных эпидемиологических исследований касательно пациентов с ВЗК -исследование ESCApе (Epidemiological Study Of Occurrence, Clinical Course And Treatment Options Of Infl ammatory Bowel Disease In Russian Federation) и ESCApе-2 [14,15]. Исследование ESCApе было проведено в период 2011 года и охватывало данные о 1254 пациентах с язвенным колитом и 543 пациентах с болезнью Крона из 21 гастроэнтерологического центра 18-ти регионов РФ.…”
Section: обсуждение результатовunclassified
“…У больных Пс нередко развиваются периферический артрит, поражение осевого скелета, энтезит, теносиновит, дактилит, при этом в 20% случаев суставные проявления предшествуют поражению кожи [20]. Многообразие клинических проявлений болезни Крона (БК) определяется поражением любого отдела желудочно-кишечного тракта (ЖКТ) и частым развитием осложнений (свищей и стриктур), что затрудняет диагностику на ранних стадиях, до развития осложнений, и может существенно повлиять на результаты лечения, а также отдаленные исходы заболевания [21][22][23].…”
Section: процесс формирования согласительных рекомендацийunclassified
“…В то же время у ряда больных диагностика затягивается на десятилетия (до 420 мес при ЯК и 480 мес при БК). Обращает на себя внимание то, что в среднем диагноз БК устанавливался гораздо позже диагноза ЯК [22]. По данным О.Б.…”
Section: процесс формирования согласительных рекомендацийunclassified